MODEL DISTRIBUSI LIMBAH BOD5 TERSEBAR (NONPOINT SOURCE POLLUTION-BOD) DI PERAIRAN LAUT PULAU BULUH KOTA BATAM KEPULAUAN RIAU - Haerizul Fahrullah; Zulkarnaini Zulkarnaini; Syahril Syahril (Jurnal Ilmu Lingkungan, 2018)
Background and Purpose: The large number of shipyard industrial activities that stand around Buluh Island has the potential to pollute the waters of the island of Buluh so that it impacts on the catches of the reed island fishermen themselves. Some electronic media reported the impact felt by the fishermen of Buluh Island on the shipyard industry and farm of pig activities. This study aims to maintain the quality of the aquatic environment on Batam City's Buluh Island through the modeling of sources of scattered waste, so a study of non-point pollution is needed that has a direct impact on people's lives. Material and Methods: BOD parameters, in general are widely used to determine the level of waste water pollution. BOD measurement is a measurement of the amount of oxygen used by microorganisms in decomposing organic matter that is in a waters. Decomposition of organic matter involves various organisms and oxidation reactions occur with the end result of carbon dioxide (CO2) and water (H2O). Oxidation reactions during the BOD examination are the result of biological activity and the reactions that take place are influenced by the population and temperature. This research was conducted in the Buluh Island area, Bulang District, Batam City, Riau Islands Province. This research was conducted in April - June 2019. The location of the study was Buluh Island, where there were many shipyards and pigs which were thought to be a source of waste distributed in the marine waters of the island of Batam City. Sampling is done based on the station (5 stations) that have been determined and measured in the laboratory and compared with the results of the model using equation 1. Results: Based on the results obtained at the five stations both for measurement results and modeling results (calculation results) BOD concentration values the highest is at station-3 and station-5 with values 16,978 and mg / L.17, 986 mg / L. This is because the station is the main source of waste in the farm of pigs and the location of the largest shipyard in the study area which has an impact on the decline in catches of Batam Island's Buluh fishermen. Conclusion: Based on the analysis conducted in this study, it can be concluded that by using the equation of the distribution model of scattered limbs and some physical parameters such as current speed, distance, coordinates and some water samples at each station, it is very easy to map the BOD-wide waste distribution model in Buluh Island waters. Batam City, Riau Islands.